Arctic archaeology
1 online resource (180 pages)
Keywords: Examining human occupation of the arctic and subarctic zones, irrespective of place and time, this book explores a wide variety of fascinating areas and inhabitants along several points in history. Beautifully illustrated, Arctic Archaeology is essential reading for all those curious about how organisms survived in this life threatening environment.